Densely functionalised spirocyclic oxetane-piperidine scaffolds for drug discovery. Issue 4 (15th February 2018) - Geary, Gemma C.; Nortcliffe, Andrew; Pearce, Christopher A.; Hamza, Daniel; Jones, Geraint; Moody, Christopher J.
Graphical abstract: Gold catalysed rearrangement of a propargylic alcohol leads to densely finctionaised spirocyclic oxetane-piperidine scaffolds for drug discovery. Abstract: A spirocyclic, sp 3 -atom rich oxetane-containing scaffold was synthesised in just two steps via a gold catalysed propargylic alcohol rearrangement. The key gold cyclisation can be undertaken on a 40 g scale allowing the preparation of 419 lead-like compounds based on the scaffold for the European Lead Factory.